2016
DOI: 10.1177/0310057x1604400212
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury following Liver Transplantation: A Systematic Review of Published Predictive Models

Abstract: Acute kidney injury (AKI) is a frequent postoperative complication amongst liver transplant recipients and is associated with increased morbidity and mortality. This systematic review analysed the existing predictive models, in order to solidify current understanding. Articles were selected for inclusion if they described the primary development of a clinical prediction model (either an algorithm or risk score) to predict AKI post liver transplantation. The database search yielded a total of seven studies desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 62 publications
0
30
0
1
Order By: Relevance
“…The definition of AKI itself is also not standardised in the literature, which adds further complexity to this subject. Additionally, commonly used surrogates of renal function may have reduced accuracy in end-stage liver disease; serum creatinine levels can be misleadingly low and blood urea nitrogen levels can be artificially low or high 6 .…”
Section: Evaluation Of Perioperative Predictors Of Acute Kidney Injurmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of AKI itself is also not standardised in the literature, which adds further complexity to this subject. Additionally, commonly used surrogates of renal function may have reduced accuracy in end-stage liver disease; serum creatinine levels can be misleadingly low and blood urea nitrogen levels can be artificially low or high 6 .…”
Section: Evaluation Of Perioperative Predictors Of Acute Kidney Injurmentioning
confidence: 99%
“…The aforementioned difficulties in measuring and defining renal dysfunction make comparison of separate studies more Correspondence complicated. In fact, several authors of predictive models for AKI post LT have not included any surrogate for preoperative renal dysfunction, as is highlighted in the recent literature review by Caragata et al 6 . Furthermore, multiple studies have shown that post LT renal impairment also occurs frequently in patients with normal baseline renal function 6 .…”
Section: Evaluation Of Perioperative Predictors Of Acute Kidney Injurmentioning
confidence: 99%
“…There are several (mostly single center) studies outlining frequency, risk factors or outcomes of AKI in immediate post-transplant period [10, 15]. However, there are limited data on the epidemiology of trends in AKI over time, particularly severe AKI requiring dialysis (AKI-D), in all hospitalizations among orthotopic cardiac and liver transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Использование стандартных классификаций для диагностики и стратификации ОПП способствовало повышению выявляемости данного синдрома в клинической практике и эпидемиологических исследованиях [5]. R. Caragata et al [51] указывают на постепенные изменения в понятии ОПП и подчеркивают необходимость использования стандартизированного определения в последующих исследованиях. Классификации ОПП по критериям AKIN, RIFLE и KDIGO позволяют оценить тяжесть дисфункции почек у пациентов после ТП [52].…”
Section: диагностика острого повреждения почекunclassified